Influence of Weight Loss on Obesity‐Associated Complications After Metabolic and Bariatric Surgery in Adolescents. Issue 12 (24th November 2020) - Derderian, S. Christopher; Patten, Luke; Kaizer, Alexander M.; Moore, Jaime M.; Ogle, Sarah; Jenkins, Todd M.; Michalsky, Marc P.; Mitchell, James E.; Bjornstad, Petter; Dixon, John B.; Inge, Thomas H.
Abstract : Objective: Following metabolic and bariatric surgery (MBS), most adolescents experience weight loss and improvement of many obesity‐associated complications (OACs). The relationship between weight loss and remission of OACs after MBS in adolescents has not been well described. Methods: The Teen Longitudinal Assessment of Bariatric Surgery (Teen‐LABS) is a multi‐institutional prospective observational study of adolescents who underwent MBS between 2007 and 2012. Lower‐weight‐loss responders (LWLRs) were defined as having <20% total body weight loss (TBWL) and higher‐weight‐loss responders (HWLRs) were defined as having ≥20% TBWL at 5 years after MBS. The prevalence of OACs was compared at baseline and 5 years after MBS. Results: Both LWLRs ( n = 114) and HWLRs ( n = 78) lost significant weight within the first year following MBS; however, the TBWL at 5 years for the LWLRs was 8.6% ± 9.5% compared with 33.8% ± 9.2% for the HWLRs. Those in the HWLR group were more likely to experience durable remission of composite dyslipidemia at 5 years, whereas there were no differences between groups in remission rates of all other OACs. Conclusions: Greater weight loss after MBS in adolescents was associated with greater remission of composite dyslipidemia; however, remission of other OACs was not dependent on major sustained weight loss.